von Willebrand Factor without the A2 Domain Is Resistant to Proteolysis - Lankhof, Hanneke; Damas, Conchi; Schiphorst, Marion E; Ijsseldijk, Martin J W; Bracke, Madelon; Furlan, Miha; Tsai, Han-Mou; de Groot, Philip G; Sixma, Jan J; Vink, Tom (Thrombosis and Haemostasis, 1997)
von Willebrand factor (vWF) is a complex multimeric plasma glycoprotein, that plays a critical role in the mediation of platelet adhesion to the damaged vascular wall, and functions as a carrier protein for factor VIII. vWF has a domain structure consisting of repeated A, B, C, and D domains. The A1 domain is involved in binding to the platelet receptor glycoprotein (GP) lb, and the A3 domain has a binding site for collagen. A function of the A2 domain has not been described, although point mutations identified in von Willebrand disease (vWD) type 2A patients are localized in this domain. To study the role of the A2 domain a deletion mutant was constructed which lacked the A2 domain, ΔA2- vWF. Previous studies have shown that this approach is a powerful tool to study the function of a domain in a protein since it does not affect the activity of other domains. After expression in baby hamster kidney (BHK) cells, ΔA2-vWF was compared to wild-type (WT) vWF, and to ΔAl-vWF (Lankhof et al., Blood 86: 1035,1995). Ristocetin induced platelet binding was slightly increased but botrocetin induced platelet binding was normal as was binding to heparin and collagen type III. Adhesion studies to surface coated purified ΔA2-vWF or to ΔA2-vWF preincubated on collagen under flow conditions showed no abnormalities. Incubation with normal human plasma showed that ΔA2-vWF like WT-vWF was not sensitive to proteolysis. After addition of urea, WT-vWF becomes sensitive to the protease, indicating that unfolding of the molecule is necessary for exposure of the cleavage site. ΔA2- vWF tested under the same conditions was resistant, indicating that the protease sensitive site is located in the A2 domain.